Inhibitory effect of erythromycin on interleukin 8 production by 1 alpha,25-dihydroxyvitamin D3-stimulated THP-1 cells. - Fujii, T (1996)
We have recently reported that long-term administration of erythromycin at a low dose reduced the number of neutrophils and concentrations of interleukin 8 (IL-8) in bronchoalveolar lavage fluid in patients with chronic lower respiratory tract disease. To investigate the mechanism of action of erythromycin, we evaluated its effect on IL-8 production in the 1 alpha,25-dihydroxyvitamin D3-stimulated human monocytic cell line THP-1. Erythromycin at a concentration of 10 micrograms/ml significantly reduced IL-8 production by THP-1 cells stimulated with lipopolysaccharide (10 ng/ml) and 1% normal human serum compared with the amount produced by untreated cells (untreated cells, 2,448 pg/ml; erythromycin-treated cells, 872 pg/ml). Our results suggest that erythromycin may impair IL-8 production by alveolar macrophages, ultimately reducing neutrophil accumulation in the airspace.